Seroprevalencia de marcadores de infecciones transmisibles por vía transfusional en banco de sangre de Colombia (2012)
ABSTRACT : OBJECTIVE: To determine the seroprevalence of markers of transfusion transmissible infections in donors of a blood bank in Medellin, Colombia, beteween 2007 and 2010. METHODS: A cross-sectional secondary data source, based on the results of biological testing of donors to a blood bank in Medellin. We determined the seroprevalence of markers of infection and were compared by sex and type of donor through frequency analysis, chi square, Fisher and prevalence ratios. RESULTS: The base population was 65,535 donors, and 3.3% had at least one positive biological test. The most prevalent marker in the blood bank testing was syphilis (1.2%), followed by trypanosomiasis (1.0%), hepatitis C virus (HCV) (0.6%), human immunodefi ciency virus (HIV) 0.5% and hepatitis B virus (HBV) (0.2%). Based on the reference laboratory found a prevalence of 0.6% for syphilis, 0.1% for (HBV) and 0% for (HCV), (HIV) and Chagas. We found statistical differences in the prevalence of (HBV) and syphilis by sex and type of donor. CONCLUSIONS: The results are consistent with the prevalences given by Pan American Health Organization and can be correlated with the global prevalence of transfusion-transmitted infections. The results founds by the blood bank lead to a transfusion risk reduction but limit the optimization of resources by excluding donors classifi ed as false positives.